The relationship between economic growth and selected macroeconomic indicators in a group of Central and East European countries: A panel data approach - Çiftçio?lu, Serhan; Begovic, Nermin (LLC CPC Business Perspectives, 2008)
The paper investigates the relationship between economic growth and various macroeconomic indicators using panel data set of a selected group of 9 Central and East European Countries over 1995-2003. The choice of appropriate econometric model for each growth regression in relation to specific indicator is made based on the results of specification tests that include Hausman, Lagrange Multiplier and F tests. The main findings are as follows: Both the level of inflation rate and its volatility negatively affect economic growth: ? the share of domestic investment in GDP has positive impact on growth rate of GDP; ? 'openness' when measured as the ratio of the sum of exports and imports to GDP positively affects economic growth; ? the ratio of the stock of external debt to GDP exerts a negative impact on economic growth; ? the ratio of budget balance to GDP is likely to positively affect growth rate of GDP. © Serhan Ciftcioglu, Nermin Begovic, 2008.
Keywords: Budget balance; Economic growth; External debt; Inflation; Investment; Openness